2018
DOI: 10.1016/j.ijheh.2017.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Platinum, palladium, rhodium, molybdenum and strontium in blood of urban women in nine countries

Abstract: General population blood concentrations of Pt, Pd and Rh are within or below the single digit ng/L range, much lower than in most previous reports. This is probably due to improved analytical performance, allowing for more reliable information at ultra-trace levels. In general, Mo and Sr agreed with previously reported concentrations. All elements showed geographical and inter-individual variations, but no convincing relationships with self-reported traffic intensity were found. Pt from the antineoplastic drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…V České republice byla v rámci MZSO získána řada výsledků, které umožnily účast SZÚ v mnoha mezinárodních projektech např. PHIME, ESBIO a COPHES-DEMOCOPHES, jejichž výsledky byly publikovány v mezinárodních prestižních časopisech (7)(8)(9).…”
Section: úVodunclassified
“…V České republice byla v rámci MZSO získána řada výsledků, které umožnily účast SZÚ v mnoha mezinárodních projektech např. PHIME, ESBIO a COPHES-DEMOCOPHES, jejichž výsledky byly publikovány v mezinárodních prestižních časopisech (7)(8)(9).…”
Section: úVodunclassified
“…However, the increased use of PGEs as components of autocatalytic converters attached to motor vehicles has resulted in the urban environment being seriously polluted by Pt. Several studies have suggested that PGEs and their complexes in airborne particulate matter (PM) may be one of the causes of health disorders such as asthma, allergies, and rhinoconjunctivitis [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, platinum levels persist many years after anticancer treatment in the blood of urban women. 26…”
Section: Introductionmentioning
confidence: 99%
“…The long-term storage of Cd by MT in the kidneys raises the question about whether these xenobiotic metals will follow this pathway and bioaccumulate. For instance, platinum levels persist many years after anticancer treatment in the blood of urban women …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation